Organizational Decisions in Multistage Production Processes - Verena Nowak (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
To explain organizational decisions in multistage production processes we assume a production process with one producer and two suppliers of which one is the firm's direct supplier and the other one is the supplier of the supplier. The firm decides only on the organizational form of her direct supplier who in turn decides on the organizational form of his supplier. Analyzing a scenario of simultaneous production, we find that the decision of the supplier - whether to integrate or outsource his own supplier - is independent from the organizational decision of the producer with respect to her supplier. However, once the production decisions of the firm and the suppliers are made sequentially, the supplier's organizational decisions is no longer independent from that of the producer. More precisely, the supplier's decision to integrate or outsource his own supplier additionally depends on the elasticity of demand and on the importance of the producer for the production process.
Keywords: D23; L22; L14; 330